Maturogenesis. Part I. Introduction, Stem Cells, Growth Factors and Matrix - R. Žižka; J. Šedý; J. Škrdlant; N. Němcová (Czech Dental Chamber, 2016)
Objectives: Endodontic treatment of immature permanent tooth with necrotic pulp is one of the most challenging treatment options in endodontics. Even when the standard treatment modalities like calcium hydroxide apexification or MTA plug are succesfull, the long term prognosis of teeth is rather to be poor. It is because of thin root canal walls, which are prone to fracture. The great progress has been achieved in last two decades in the field of tissue engineering which leads to novel treatment strategies. Its aim is formation at new vital tissue inside of root canal system. This new tissue should be able to produce hard tissue, that leads to thickening of root canal wall and further development of root apex. In these reviews we would like to summarize available literature about another possible treatment modality. Maturogenesis is based on the principles of tissue engineering and can be perfomed by every general practitioner.This first part is concerned the introduction to the treatment problem of immature permamenent teeth with necrotic pulp including anatomical differencies. Furthermore, particular parts of tissue engineering concept - stem cells, growth factors and matrices which can play role in maturogenesis have been analysed.